Site-specific ground motions for seismic design of buildings and other structures - Malhotra, Praveen K. (American Society of Civil Engineers, 2022)
Earthquake ground motions are at the interface of two disciplines - seismologists predict them, and engineers use them. Oftentimes, engineers do not understand the limitations of ground motion prediction, and seismologists do not understand the effect of ground motions on structures. As a result, there is significant confusion regarding ground motions for design.Site-Specific Ground Motions for Seismic Design of Buildings and Other Structures provides a step-by-step approach to properly conduct site-specific Ground Motion Hazard Analysis (GMHA) and Site Response Analysis (SRA). This book also explains various resources that are available to perform GMHA and SRA. It references several standards to provide a comprehensive approach to generate ground motions for design.Topics includeBackground of design ground motions in the United States,General Procedure (GP) in ASCE 7 and its limitations,Ground Motion Hazard Analysis,Site Response Analysis,Ground motions for the evaluation and retrofit of buildings (ASCE 41),Ground motions for the design of LNG tanks (ACI 376 and API 620 & 625),Ground motions for the design of bridges (AASHTO and Caltrans), andGround motions for the performance-based design of tall buildings (PEER TBI).This book will appeal to geotechnical and structural engineers who need ground motion parameters for liquefaction analyses and seismic design of structures. It will also be highly useful to seismologists, geologists, educators, students, and building code officials.About the AuthorDr. Praveen K. Malhotra, P.E. has worked alongside eminent geologists and seismologists for many years and founded his own consulting company, StrongMotions Inc. He is an author and presenter, as well as a trainer for seismic topics for ASCE in the United States and worldwide.
Keywords: Earthquake hazard analysis -- Mathematical models.; Soils -- United States -- Testing.; Seismology -- United States.; Structural engineering -- Standards -- United States.; Earthquake resistant design -- United States.; elektronické knihy; electronic books